Synthesis, Characterization And Anti-Proliferation Study Of Some Benzimidazole Derivatives - al-Douh, Mohammed Hadi Saeed (2010)

(untitled)
Four different types of compounds were successfully synthesized and characterized. The syntheses of these compounds involved benzylation, addition elimination and cyclization reactions. The structures of the synthesized compounds were confirmed by melting points, FTIR, HRMS, 1D and 2D NMR spectroscopy and X–ray crystallography. The first type of these compounds is 2-benzyloxy-3- methoxybenzaldehyde 75, which was synthesized by the reaction of o-vanillin with benzyl bromide in acetone as the solvent and K2CO3 as a base in the presence of tetra-n-butylammonium iodide (TBAI) as catalyst.